2014
DOI: 10.4103/0976-7800.133988
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological diseases in rural India: A critical appraisal of indications and route of surgery along with histopathology correlation of 922 women undergoing major gynecological surgery

Abstract: Objective:The aim of the study was to generate baseline data for indications of gynecological surgeries, and to assess route of surgery and histopathology correlation in women undergoing major gynecological surgery in a rural tertiary level teaching hospital in India.Materials and Methods:Surgical indications, route of surgery and histopathology findings were reviewed and analyzed retrospectively, in 922 patients (≥35 years age) who underwent gynecological surgery at Dr. Rajendra Prasad Government Medical Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 18 publications
(21 reference statements)
10
21
0
Order By: Relevance
“…We observed that there was very little awareness about NDVH and its outcome among the subjects well comparable with the study by Sharma et al [12] and Amarjeet et al [13]. In our study out of 100 patients, ten were adamant and refused NDVH and underwent TAH.…”
Section: Resultssupporting
confidence: 89%
“…We observed that there was very little awareness about NDVH and its outcome among the subjects well comparable with the study by Sharma et al [12] and Amarjeet et al [13]. In our study out of 100 patients, ten were adamant and refused NDVH and underwent TAH.…”
Section: Resultssupporting
confidence: 89%
“…In many areas (especially, rural areas) here in India and in other developing countries, poverty, lack of regular follow-up, resource constraints and lack of technical skills pose major challenges in providing quality health care. 10 Therefore, results of this study cannot be generalized. Secondly, it is possible that both the SAS assigned and the patient's risk for postoperative outcomes per se were influenced by confounding factors such as the use of beta-blockers, intraoperative resuscitation and ascites.…”
Section: Discussionmentioning
confidence: 72%
“…16,[18][19][20][21] However, there has been controversy regarding indications for hysterectomy for benign gynecological diseases in Indian subcontinent. 22 Of total, only 6% surgeries were done for premalignant cervical lesions in the study which conclude that rural women with cervical malignancy usually present late due to lack of awareness, non availability of adequate screening tests and pathologists. Thus surgery for malignant disease is life-saving, whereas for that benign disease to improve the quality of life, hence hysterectomy is not only a cost-effective but also associated with excellent satisfaction as compared to conservative therapies.…”
Section: Discussionmentioning
confidence: 99%